Carbon dioxide equivalent emissions of newly developed rice varieties - Taghavi, Seied Mohsen; Mendoza, Teodoro C.; Acero Jr, Bart; Li, Tao; Siddiq, Sameer Ali; Yorobe Jr, Jose; Li, Zhikang; Ali, Jauhar (Cambridge University Press, 2017)
Breeding of rice varieties with low carbon dioxide equivalent (CO2e) emission is essential in reducing global greenhouse gas (GHG) emissions. In this study, we compared the gross CO2e emission of two newly developed green super rice (GSR) varieties with elite hybrids and nationally released farmer-cultivated varieties from production to post-production in the dry and wet seasons in Laguna, Philippines. The average gross CO2e emission was 17.9 tons CO2e ha-1 or 2.98 tons CO2e ton-1 rice (production 82%, post-production 18%). Contributing to this total were soil emissions at 72%, the use of chemicals at 5%, burning of rice straw at 3%, cooking at 12%, and transportation at 5%. The average social cost of carbon (SCC) per ton of rice was estimated at $119. Increasing grain yield per unit area with shorter growth duration decreased CO2e emission of rice per unit of weight. Cultivation of rice varieties GSR8 and GSR2 emitted 37.0% lower CO2e than the popular inbred varieties.